Recent progress in cassava varietal improvement in the Philippines - Mariscal, Algerico M.; Bergantin, Reynaldo V. (International Center for Tropical Agriculture, 1998)
In recent years cassava has become an important raw material for various domestic needs (food, feed, alcohol and high fructose sugar). To cope with high demand for cassava roots the breeding and selection program has been intensified to identify varieties that are high yielding and having high starch and dry matter contents. The continuous introduction of improved cassava populations from the Thai-CIAT program and from CIAT/Colombia contributed to the identification of good varieties, and, consequently, the establishment of cassava genepools having a wide genetic base. This has led to the establishment of a breeding program using the best parents of local and foreign sources.